NEW CELLULOSIC BASED ACOUSTIC WALL BOARD MATERIAL FROM PAPER WASTE - RAZALI, LUQMAN HAKIM (2011)
PAPER WASTE IS A COMMON POLLUTION THAT ENCOUNTER BY THE WORLD NOWADAYS. THE PAPER INDUSTRY RANKS 4TH IN CONTRIBUTION TO GREENHOUSE EMISSION. THE STUDT FOCUS ON TWO POINTS WHICH AREE PROPERTIES OF THE NEW CELLULOSIC MATERIAL AFTER COMBINED WITH FIBER AND THE BEST FIBER ORIENTATION TO USE AS AN ACOUSTIC WALL.